2003
DOI: 10.1590/s0102-86502003000300011
|View full text |Cite
|
Sign up to set email alerts
|

Uso de quercetina a longo prazo em ratos cirróticos

Abstract: IntroduçãoCirrose é uma doença crônica que acomete difusamente o fígado sem envolver necessariamente todos os lóbulos hepáticos, sendo histologicamente

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
2
3
0
3
Order By: Relevance
“…All dosages of quercetin decreased AST levels in the serum of arthritic rats, demonstrating the hepatoprotective potential effect of this flavonoid. This effect has been verified in other studies, and it is suggested to be due to the antioxidant capacity of quercetin through the elimination of reactive oxygen species, inhibition of lipoxygenase and cyclooxygenase, and stabilization of cell membranes …”
Section: Discussionsupporting
confidence: 68%
“…All dosages of quercetin decreased AST levels in the serum of arthritic rats, demonstrating the hepatoprotective potential effect of this flavonoid. This effect has been verified in other studies, and it is suggested to be due to the antioxidant capacity of quercetin through the elimination of reactive oxygen species, inhibition of lipoxygenase and cyclooxygenase, and stabilization of cell membranes …”
Section: Discussionsupporting
confidence: 68%
“…Studies by Kontouras et al (14) showed that 15 days after bile duct ligation (BDL), the metabolic and biochemical changes were not fully established. Thus, in our experiment, the animals were sacrificed only after 28 days of BDL, when studies confirmed liver cirrhosis (17,29) . In this study, both the BDL and the CCl 4 caused liver damage and elevated serum levels of AST, ALT and ALP, which are commonly known to be markers of liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Essa fase do experimento serviu também para padronizar o manejo e todos os procedimentos necessários para a realização deste estudo. A via intraperitoneal tem sido amplamente utilizada em pequenos roedores de experimentação (OLIVEIRA et al, 2002;MILTERSTEINER et al, 2003;RAMALHO et al, 2003;MAZZANTI et al, 2004), por isso foi a escolhida neste estudo, já que a via de administração do sulfato de vincristina preconizada para os animais domésticos é a intravenosa (ANDRADE, 2002). A via intraperitoneal em ratos é classicamente utilizada para substituir a via intravenosa, dadas as dificuldades da utilização desta última via.…”
Section: Methodsunclassified